Utilizing Facebook Groups in Teaching English as Foreign Language: Indonesian EFL Teachers’ Voices - Puput Arfiandhani (International Journal of Language Teaching and Education, 2020)
In the era of 4.0, social media has become an integral part of everyday life, including for the purpose of teacher learning. One of the means of social media that has been used for enhancing teachers’ independent professionalism is Facebook Groups related with their teaching professions. The present qualitative study aims at (i) exploring English as A Foreign Language (EFL) teachers’ experiences in utilizing Facebook Groups for their teacher learning and (ii) finding out the benefits of teachers’ involvement in teaching-related Facebook Groups. In collecting the data for the present case study, in-depth interviews were done with two teachers, one novice teacher and one experienced teacher. The findings and discussions indicated that teachers use Facebook groups to enhance their professionalism, despite they tend to start refraining from utilizing the groups due to uncomfortable atmosphere that Facebook now offers. Additionally there are three benefits found of joining Facebook groups, namely their enriched information on content knowledge, knowledge of curriculum and knowledge of educational contexts. In the current time where teachers need to shift into distance learning in the timely fashion, whereas many subjects need to be comprehended quickly.